Chryseobacterium gleum catheter-related blood stream infection: a case report and a review of literature - Zakaria, Nor Fadhlina (Discover STM Publishing, 2021)
Background: Chryseobacterium (Flavo.) gleum is a rare organism causing catheter-related bloodstream infections. The organism is primarily found on moist hospital surfaces, like washbasins and dressing trolleys. It has been described as the agent for bacteremia, pneumonia, and skin and soft tissue infections in clinical settings. Case Presentation: We report the case of a 60-year-old man with end-stage kidney disease, who presented with fever, chills, and rigours at the third hours of dialysis session, associated with intradialytic hypotension. The patient underwent dialysis using a left subclavian cuffed catheter, after multiple failures of fistula formations previously. Diagnosis of catheter-related bloodstream infection was made, and blood culture showed C. Gleum from both catheters' lumens. The patient showed improvement with intravenous Ciprofloxacin and tablet bactrim. Culture became negative after treatment and catheter was saved. Conclusion: Chryseobacterium gleum is an emerging pathogen that causes healthcare-associated infection for people with indwelling hemodialysis catheters. The condition poses a diagnostic and therapeutic challenge since it has been resistant to numerous broad-spectrum antibiotics. However, early management of the disease with correct antibiotics results in better response without removing indwelling catheters.